THE IMPLEMENTATION OF SCIENTIFIC APPROACH IN TEACHING WRITING NARRATIVE TEXT AT THE FIRST GRADE OF SMAN 2 PARE - Fitriyo, Joko (LENTERA : Jurnal Pendidikan dan Pengajaran, 2019)
This research was conducted to describe the implementation of scientific approach in teaching writing narrative text at the first grade of SMA Negeri 2 Pare in terms of background, implementation, evaluation, obstacle, students’ respond, and students’ skill. In this research, the researcher used descriptive qualitative research design and the researcher as the main informant. For collecting data, the researcher used documentation, teacher’s interview guide, observation list and questionaire. The subject of the research was the first grade students of SMA Negeri 2 Pare especially X MIA-3 class which the numbers of students are 38 students as a sample. The result shows that the scientific approach was implemented by the teacher in learning because the school applying curriculum 2013. The Scientific approach through observing, questioning, exploring, associating and communicating could be implemented at SMA Negeri 2 Pare. The writing evaluation is done by do the task grouply. Too much material with only 1 meeting each weak still become the obstacle for the teacher in learning process.  More  than 65.79 % of 38 students give a good respond to the approach. The students’ skill are satisfying because all of them successfull in reaching the KKM .